Pengaruh Leverage terhadap Kinerja Keuangan Perusahaan - Murdhaningsih, Murdhaningsih; Harared, Bunga Anisah; Malik, M. Anas Hilmy (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of leverage analysis on the company's financial performance, either simultaneously or partially. Leverage analysis will be described by the debt ratio, debt to equity ratio, long-term debt to equity ratio and long-term debt to total asset ratio while the company's financial performance is measured by return on equity. The population in this study are companies listed on the Indonesian stock exchange. . The sampling method used is purposive sampling method. The research data were obtained from the sample companies which were downloaded from the Indonesian Stock Exchange website. The data analysis technique used is descriptive statistical analysis and multiple regression analysis. The results of this study prove that simultaneously the variables debt ratio, debt to equity ratio, long-term debt to equity ratio and long-term debt to total asset ratio affect return on equity. Partially, the variable debt to equity ratio and long-term debt to equity ratio have an effect on return on equity.